The relationship of job motivation toward job satisfaction at among lower level employees at Ukhwah Malaysia Berhad / Dzuhairah Dzulkifli - Dzulkifli, Dzuhairah (Faculty of Business and Management, 2013)
The study investigates the relationship between Job Motivation and Job Satisfaction. Job Motivation has been treated as an independent and Job Satisfaction as dependent variable. The selected respondents for the study are the employees at Ukhwah Malaysia Berhad. All respondents for the study are from lower level employee form Ukhwah Malaysia Berhad. The primary data was collected by the researchers tlu'ough a questiOlmaire and based on five pointer Likert scale. All data received will be analyzed by SPSS Version 18.0.